Electrochromic properties of novel octa-pinene substituted double-decker Ln(iii) (Ln = Eu, Er, Lu) phthalocyanines with distinctive near-IR absorption1. Issue 13 (7th April 2015) - Zheng, Wei; Wang, Bei-Bei; Lai, Jian-Cheng; Wan, Cheng-Zhang; Lu, Xin-Rong; Li, Cheng-Hui; You, Xiao-Zeng
<x xml:space="preserve">Abstract</x> The introduction of pinene groups into lanthanide(iii) double-decker phthalocyanines results in excellent solubility as well as nontrivial spectral and electrochemical properties. Upon external potential, the new lanthanide(iii) double-decker phthalocyanine complexes show electrochromic properties at both visible and near infrared range.